Personal and Emotional Factors in the Labour Integration of University Graduates in the Field of Education. Implications for University Teaching - Juan L. Castejón; Raquel Gilar; Pablo Miñano (Center for Educational Policy Studies Journal)
The main aim of this paper is to analyse the role of intellectual, personal and emotional competencies as well as technical knowledge - academic achievement - in the employment of university graduates, with the purpose of incorporating these competencies into training programmes developed within the European Framework of Higher Education. This study is based on an initial sample of 118 university graduates in the field of education. We have gathered information about academic achievement and the intellectual, personal and emotional traits of this sample. From these data, and given the importance of non-intellectual aspects of intelligence associated with professional success, the specific contribution -incremental validity - of personal and emotional intelligence in explaining the employment - labour integration - of university graduates in the field of education is studied. From this point onwards, we attempt to identify the key socio-emotional competencies in the field of education in order to establish the implications of including this type of skills in university training programmes within the European Higher Education Area.